FAKTOR-FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PENAWARAN TENAGA KERJA WANITA DI ACEH - Husnul Maghfirah; T. Zulham (Syiah Kuala University, 2016)
This research is motivated by the problem that many women who enter the job market. The desire of women in entering the world of work is encouraged by certain factors, particularly social and economic factors. The purpose of this study was to determine how the influence of education, inflation, and wages on women labor supply in Aceh. This study used multiple linear regression analysis. The data used in this research is secondary data. The number of years of data in this study were 15 yaers, started from 2000 to 2014. The results showed that from the variables of education, inflation, and wages, only two variables are positive and significantly impact on women labor supply in Aceh, namely education and wages. Based on the research that has been done, the level of women labor supply in Aceh is still low compared to men labor supply.